Perceived Level of Life Enjoyment and Risks of Cardiovascular Disease Incidence and Mortality: The Japan Public Health Center–Based Study - Shirai, Kokoro; Iso, Hiroyasu; Ohira, Tetsuya; Ikeda, Ai; Noda, Hiroyuki; Honjo, Kaori; Inoue, Manami; Tsugane, Shoichiro (Circulation (New York, N.Y.), 2009)
Background— Perceived level of life enjoyment, a positive psychological condition that reflects the ability to engage pleasurably with the environment, may relate to risks of cardiovascular disease. This prospective cohort study attempted to examine the effects of perceived level of life enjoyment on cardiovascular disease incidence and mortality among Japanese community residents. Methods and Results— Subjects were 88 175 Japanese men and women 40 to 69 years of age who were free of cardiovascular disease at baseline and followed up for a median of 12.0 years and were included in the Japan Public Health Center–Based (JPHC) Study Cohort. Data about psychological conditions and other confounding variables were obtained through self-administered questionnaires. Information on incidence and mortality for cardiovascular disease was collected through registered hospitals and public health centers. The multivariable hazard ratios of cardiovascular disease incidence for men in the high versus low perceived levels of life enjoyment group were 1.22 (95% confidence interval, 1.01 to 1.47) for stroke and 1.23 (95% confidence interval, 1.05 to 1.44) for total cardiovascular disease. As for mortality, Japanese men with low perceived level of life enjoyment showed increased risk: hazard ratios of 1.75 (95% confidence interval, 1.28 to 2.38) for stroke, 1.91 (95% confidence interval, 1.30 to 2.81) for coronary heart disease and 1.61 (95% confidence interval, 1.32 to 1.96) for total cardiovascular disease. For women, however, the perceived level of life enjoyment was not associated with risks of cardiovascular disease incidence or mortality. Conclusion— A lower perceived level of life enjoyment was found to be associated with higher risks of cardiovascular disease incidence and mortality among middle-aged men, suggesting a protective role of positive psychological conditions on cardiovascular disease.